Pharmacotherapeutic elements in the osteoarticular algia in dog - Calin I. HULEA; Romeo Teodor CRISTINA (Medicamentul Veterinar)
Canine osteoarthritis (OA), along with hip dysplasia (DSC) and elbow dysplasia (CDC) are diseases commonly found in veterinary practice in pet animals. Due to the fact that these conditions persist throughout life, it degenerates rather than improve, so it is extremely important that these dogs be treated in osteoarticular algia in dogs. OA is also one of the most common musculoskeletal disorders in humans that has become a medical and financial problem. Moreover, an even bigger problem is treating people suffering from the side effects that appear as a consequence of pain therapy in OA. As a result, recommendations have been made to use more natural agents in modifying the effects of the disease in the management of human OA pain, to the detriment of much more commonly used non-steroidal antiinflammatory drugs (NSAIDs). To this end, we are also investigating in college to find less harmful drugs and treatments to replace the long-term administration of NSAIDs or regenerative injections with corticosteroids, which today are still the best treatment options used, although they are not ideal because of the risk of side effects. This bibliographic report wishes to bring some valuable information to those interested.